Thoracic SMARCA4-deficient undifferentiated tumor - Jiapeng Jiang; Zhixin Chen; Jiali Gong; Na Han; Hongyang Lu (Discover Oncology, 2023)
Abstract Thoracic SMARCA4-deficient undifferentiated tumor (SMARCA4-UT) is a recently described smoking-related malignancy. The pathogenesis of SMARCA4-UT is the mutational inactivation and loss of expression of a subunit encoding the mammalian switch/sucrose nonfermenting ATPase-dependent chromatin remodeling complex (which can be mobilized using adenosine triphosphate hydrolysis nucleosomes and regulate other cellular processes including development, differentiation, proliferation, and apoptosis), in particular SMARCA4 and SMARCA2. The dynamic activity of this complex plays an important role in regulating the activation and repression of gene expression programs. SMARCA4-UT exhibits morphological features similar to the malignant rhabdoid tumor (MRT), small cell carcinoma of the ovary of the hypercalcemic type (SCCOHT), and INI1-deficient tumor, but SMARCA4-UT differs from SCCOHT and MRT from a genomic perspective. SMARCA4-UT mainly involves the mediastinum and lung parenchyma, and appears as a large infiltrative mass that easily compresses surrounding tissues. At present, chemotherapy is a common treatment, but its efficacy is not clear. Moreover, the inhibitor of the enhancer of zeste homolog 2 showed promising efficacy in some patients with SMARCA4-UT. This study aimed to review the clinical characteristics, diagnosis, treatment, and prognosis of SMARCA4-UT.